Hospital Readmissions and Mortality Among Intubated and Mechanically Ventilated Adult Subjects With Pneumonia Due to Gram-Negative Bacteria. - Lodise Jr, Thomas P.; Law, Amy; Spilsbury-Cantalupo, Monica; Liao, Laura; McCart, Melissa; Eaddy, Michael (Respiratory Care, 2021)
BACKGROUND: Ventilator-associated pneumonia (VAP) is one of the most common hospital-acquired infections in ICUs and is associated with significant morbidity and mortality. Gramnegative bacteria cause 55-85% of hospital-acquired pneumonia and are associated with increased mortality. METHODS: This study sought to describe mortality rates and 30-d readmission rates among intubated and mechanically ventilated subjects with Gram-negative pneumonia and to explore associated risk factors for mortality and rehospitalization using data from the 2013 Healthcare Cost and Utilization Project (HCUP) National Readmission Database. The study sample included adults age ≥ 18 y who were hospitalized with invasive, continuous mechanical ventilation; were discharged between February 1, 2013, and November 30, 2013; and had a primary or secondary diagnosis of Gram-negative bacterial pneumonia. Logistic regression was used to identify subject characteristics significantly associated with mortality and readmissions. RESULTS: Using the HCUP projected sample of 32,683 intubated and mechanically ventilated subjects with Gram-negative pneumonia, the mortality rate during the index hospitalization was 24.3%. More than one fifth of subjects (22.9%) who survived the index hospitalization were readmitted within 30 d of discharge. Among subjects with readmissions, 18% occurred within 3 d of discharge, 39% occurred within 7 d of discharge, and 65% occurred within 14 d of discharge. Subjects with prior hospitalization within 30 d of the index hospitalization had a higher risk of readmission with an odds ratio of 1.70 (95% CI 1.48-1.94). CONCLUSIONS: Mortality was high and readmissions were substantial among intubated and mechanically ventilated subjects with Gram-negative pneumonia.